Tanfîdhu Istirâtijiyyah al-Ta’lîm Group To Group Exchange "Tabâdul al-Majmû’ât" Litarqiyati Nashâṭi wa Natâiji Ta’alumi at-Ṭullâb. - Ramli, Lalu Abdul Aziz; Majid, Agung Nurcholis; Rahmanudin, Ii (Jurnal Alfazuna : Jurnal Pembelajaran Bahasa Arab dan Kebahasaaraban, 2023)
Purpose-This study aims to determine the increase in learning activeness and learning outcomes of 5th grade students in Nahwu material through the Group To Goup Exchange Learning Strategy. Design/Metodology/ Approach-This type of research is a Classroom Action Research (PTK). The number of students in class 5 is 16 students, while the object in this study is the application of the Group To Group Exchange Learning Strategy to improve student activeness and learning outcomes in Nahwu subjects. To obtain the necessary data, this study used interviews, observations, tests, and documentation. And analyze it with several indicators that have been formulated by the researcher. Findings-The results of this study are as follows: 1) that the application of the Group To Group Exchange Learning Strategy can increase student learning activeness in 5th grade Nahwu material at the al-ikhlas al-islamy Kaliaji Islamic boarding school in Central Lombok. In cycle I, active students were 6 students out of 16 students or 37.5% of the total number of students, while in cycle II active students were 16 students out of 16 students or 100% of the total number of students, so the increase in active students in cycle I and II was 10 students or 62.5%. 2) the application of the Group To Group Exchange Strategy can improve student learning outcomes in 5th grade Nahwu material at the al-ikhlas al-islamy Kaliaji Islamic boarding school in Central Lombok. In cycle I, there were 7 students who had reached the KKM out of 16 students or 43.75%, then the increase in student learning outcomes in cycles I and II was 9 students or 56.25% who had reached the KKM score of the total number of students. Research limitation- Therefore, the Group To Group Exchange Strategy can be used in learning Arabic to the increase in learning activeness and learning outcomes